Perception and Acceptance of Male Midwives Among Pregnant Women in Selected General Hospitals in Lagos State (British Journal of Multidisciplinary and Advanced Studies, 2024)
This research was carried out to assess the perception and acceptance of male midwives among pregnant women in selected general hospitals in Lagos State. The objectives of this study were to assess their perception and acceptance; and identify the factors influencing their acceptance of male midwives. A systematic sampling technique was used in selecting three hundred and twenty-seven (327) pregnant women, but only three hundred and twelve (312) of them were validated for the study. A self-developed questionnaire served as the primary instrument of data collection for the study, and the data collected were analyzed and presented on frequency/percentage tables and bar chart(s) using Statistical Package for Social Sciences (SPSS) version 25 and Microsoft Excel version 2010. The findings revealed an overall positive perception and good level of acceptance of male midwives among them. The factors influencing their acceptance of male midwives were availability and accessibility of male midwives (67.6%); communication and trust (64.4%); trust in the competence of male midwives (64.1%); peer and family influence (63.5%); personal comfort level with opposite gender healthcare providers (62.8%); personal beliefs and preferences (62.8%); emotional support (60.9%); availability of information and education about male midwives (60.3%); cultural beliefs and norms (59.9%); religious beliefs and practices (58.7%); and previous experiences (52.6%). The study found a significant relationship between their perception and acceptance of male midwives (p < .05); between their age and factors influencing acceptance of male midwives (p < .05). Based on these findings, the study concluded that there is a need to ensure consistency and improvement in their knowledge and perception through proper evaluation and amelioration of the factors influencing their acceptance of male midwives.